Knowledge and Attitude Towards Antibiotic Prescription among Dental Students - P.S. Gayathri; Krithika C; V. Sandhya; E.Sangeetha; T.Santhoshika; Priya Ramani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Antibiotics play a crucial role in dental practice for both prophylactic and therapeuticpurposes. Excessive consumption of antibiotics or using them unreasonably not only cause emergence ofresistant bacterial strains and hostile drug reactions but also create an economic liability on the overall healthsystem of a country.Aim: The present study was aimed to evaluate the knowledge and attitude towards usage, antibioticprescription and various concerns associated with antibiotics among dental students.Methodology: A cross sectional study was conducted using self-administrated questionnaire, through Googleforms using various social media platforms such as whatsapp, facebook among 202 dental students of thirdyear, final year, interns and postgraduates across dental colleges in Tamil Nadu, India during COVID-19pandemic lockdown period. Statistics was done and tabulated.Results: Our study results show that the majority of dental students are aware of antibiotic prescription, usesof antibiotic and antibiotic resistance.Conclusion: Though the knowledge and attitude about antibiotic prescription is high among dental students,there are still few areas where they lack adequate knowledge; these deficits can be rectified by encouragingthem to attend cde programs, conferences related to antibiotic prescription.